Rab27a-mediated protease release regulates neutrophil recruitment by allowing uropod detachment - Singh, Rajesh K (2017)
Neutrophil migration is vital for immunity and precedes effector functions such as pathogen killing. Here, we report that this process is regulated by the Rab27a GTPase, a protein known to control granule exocytosis. Rab27a-deficient (Rab27a KO) neutrophils exhibit migration defects in vitro and in vivo, and live-cell microscopy suggests that delayed uropod detachment causes the migratory defect. Surface expression of CD11b, a key adhesion molecule, is increased in chemokine-stimulated Rab27a KO neutrophils compared with the control, suggesting a turnover delay caused by a defect in elastase secretion from azurophilic granules at the rear of bone marrow polymorphonuclear leukocytes (BM-PMNs). We suggest that Rab27a-dependent protease secretion regulates neutrophil migration through proteolysis-dependent de-adhesion of uropods, a mechanism that could be conserved in cell migration and invasion.